2021
DOI: 10.3389/fgene.2021.642327
|View full text |Cite
|
Sign up to set email alerts
|

MEF2C Common Genetic Variation Is Associated With Different Aspects of Cognition in Non-Hispanic White and Caribbean Hispanic Non-demented Older Adults

Abstract: ObjectivesMyocyte Enhancer Factor 2C (MEF2C) is identified as a candidate gene contributing to the risk of developing Alzheimer’s disease. However, little is known about whether MEF2C plays a role in specific aspects of cognition among older adults. The current study investigated the association of common variants in the MEF2C gene with four cognitive domains including memory, visuospatial functioning, processing speed and language among non-demented individuals.MethodParticipants from two ethnic groups, Non-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…D′ values were calculated as D/D max , where D is the coefficient of LD ranging from −0.25 to 0.25. In general, the standardized value of D′ is preferred because D is often affected by allelic frequencies ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…D′ values were calculated as D/D max , where D is the coefficient of LD ranging from −0.25 to 0.25. In general, the standardized value of D′ is preferred because D is often affected by allelic frequencies ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies found MEF2C gene as risk factor for multiple neurological disorders, such as Late Onset Alzheimer's disease (LOAD) and Parkinson's disease [41][42][43][44].…”
Section: Genes Of Interest During Stage 2 To Stagementioning
confidence: 99%